2019
DOI: 10.1016/j.coelec.2018.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuating Hydrodynamics and Debye-Hückel-Onsager Theory for Electrolytes

Abstract: We apply fluctuating hydrodynamics to strong electrolyte mixtures to compute the concentration corrections for chemical potential, diffusivity, and conductivity. We show these corrections to be in agreement with the limiting laws of Debye, Hückel, and Onsager. We compute explicit corrections for a symmetric ternary mixture and find that the co-ion Maxwell-Stefan diffusion coefficients can be negative, in agreement with experimental findings.Due to the long-range nature of Coulomb forces between ions it is well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 38 publications
1
43
0
Order By: Relevance
“…It can be confirmed that the electroneutral equations (3,4,7,18) are consistent with (31), which demonstrates that nothing special needs to be done in the electroneutral limit to handle the fluctuating diffusive fluxes except to include them in the right-hand side of the modified Poisson equation (18).…”
Section: Thermal Fluctuationssupporting
confidence: 66%
See 2 more Smart Citations
“…It can be confirmed that the electroneutral equations (3,4,7,18) are consistent with (31), which demonstrates that nothing special needs to be done in the electroneutral limit to handle the fluctuating diffusive fluxes except to include them in the right-hand side of the modified Poisson equation (18).…”
Section: Thermal Fluctuationssupporting
confidence: 66%
“…It is given by the solution of the modified elliptic equation (18), and not by the quasielectrostatic Poisson equation (2). In summary, the fluctuating electroneutral equations we consider in this work are given by (3,4,7,18).…”
Section: Electroneutral Elliptic Equationmentioning
confidence: 99%
See 1 more Smart Citation
“…As for the fluid, we can update the continuity equation Eq. ( 4) for each species α with a stochastic term [218,226,227]…”
Section: Top-down Approachesmentioning
confidence: 99%
“…Such a formulation is interesting as it allows one to efficiently investigate fluctuationdriven behavior, both numerically and analytically. Importantly, this approach has been used to identify enhanced charge transport due to fluid fluctuations, that result in ion concentration corrections to diffusion, sometimes leading to negative diffu-sion [226] or enhanced electric conductivity [229]. In other contexts, giant instabilities may appear at interfaces with concentration gradients, that can be enhanced by applied electric fields [230].…”
Section: Top-down Approachesmentioning
confidence: 99%